Indicators to Evaluate the Institutional Effectiveness of National Climate Financing Mechanisms - Sheriffdeen, Muhammad; Nurrochmat, Dodik Ridho; Perdinan, Perdinan; Di Gregorio, Monica (Forestry Faculty, Universitas Hasanuddin, 2020)
Over the past few decades, tackling climate change has persistently featured in international discussions, with the main issues centring on mobilising adequate global response and effectively coordinating and channelling this response at the sub-national levels. In order to effectively mobilize and harmonize resources to address climate change at country level, the idea of establishing national climate finance institutions (NCFIs) with the duty to mobilise, manage and allocate funds to implement climate change actions has gained prominence among developing countries. This study develops an indicator-based framework to evaluate the institutional effectiveness of the Indonesian Climate Change Trust Fund (ICCTF) as a case study. Building on previous frameworks and principles of climate finance, a total of 21 indicators were identified, these indicators were categorized into five effectiveness components, which are: were identified, and these indicators were categorized into five effectiveness components, which include: legal and regulatory framework, fund mobilization and sustainability, fund management and allocation, monitoring and evaluation, and transparency and accountability. We find that the major and fundamental weakness of the ICCTF is its inability to adequately mobilize funds, while its strength is in management and allocation of available resources. Inclusion of the legal and regulatory framework component, which has been largely absent in previous studies, further enabled us to identify critical legal gaps in the operationalization of the ICCTF. While the current legal foundation of the ICCTF ensures transparency and accountability, it significantly constrains the ICCTFs flexibility and innovative potentials.